AKTIVITAS MATA PENCAHARIAN HIDUP ETNIS TOGUTIL DI DESA LELILEF WAIBULEN KECAMATAN WEDA TENGAH KABUPATEN HALMAHERA TENGAH - Risnawati (Universitas Sam Ratulangi, 2022)
Ethnicity in Indonesia can be found in every society with a wide variety of cultures and customs. From these differences, these ethnicities or tribes can adapt and influence so that they experience the development of a simple society to a more complex society. But it turns out that there are still ethnicities whose lives are primitive and backward and far from a touch of modernization. Ethnicities who are not familiar with modern technology, their lives that depend on nature and are backward are one of the alienated ethnicities living in the interior of Halmahera island, North Maluku Province, namely the Togutil ethnicity. Nomadic life will make their living needs meet if there is still a forest that can be used as a place to hunt and concoct. In order for the activities of the Togutil ethnicity to be as before, they had to find another place to live in terms of forests that had not been evicted. Considering, many of their activities are endangered since the eviction of forests by logging and mining companies around the Lelilef Waibulen Village area, Central Weda District of the Central Halmahera Regency, which does not necessarily provide housing for the Togutil ethnicity. The Togutil people have a system of survival strategies by means of an inherent Imakiriwo culture, shoulder to shoulder to care for and safeguard the remaining natural resources and still maintain their livelihoods by hunting and gathering and still being able to live by getting out of settlements and bartering. Keywords: activity, nomadic, survival